Content structure is king: An empirical study on gratifications, game genres and content type on Twitch. (August 2017) - Sjöblom, Max; Törhönen, Maria; Hamari, Juho; Macey, Joseph
Abstract: While video games have been widely investigated from the perspective of play, an emerging online media phenomenon is the spectating of video game play, captivating millions of users daily. This study investigates the relationship of video game genres, content type and viewer gratification in the context of live gaming. To study this phenomenon, we employ an online questionnaire study (N = 1097) to investigate six categories of gratifications: affective, information seeking, learning to play, personal integrative, social integrative & tension release motivations and their relationship with game genres and stream types. The results of this study demonstrate that "the medium is the message", highlight the importance of archetypal structure (i.e. the type of streamed content) over content topic (i.e. the genre of games being streamed), and help to build a better understanding of user generated content and the democratization of media. Highlights: This study helps understand the relation between content type and topic. Content structure is shown to be more important than content topic for consumption. The results indicate that, indeed, "the medium is the message". Games may offer highly varying gratifications when played and when spectated.